A cross-cultural investigation of the short version of the Celebrity Attitude Scale (CAS-7) across five countries - Rita Horvath; David C. Watson; Lynn McCutcheon; Yohanes Budiarto; Róbert Urbán; Zsolt Demetrovics; Fransisca Iriani Roesmala Dewi; Reza Shabahang; Benyamin Mokhtari Chirani; Joshua L. Williams; Carlota Cruces Serrano; Nancy G. McCarley; et al. (PLoS ONE, 2025)
Background Celebrity worship, conceptualized as an obsessive admiration of celebrities, has generated considerable research interest over the past two decades. Admiration towards a favorite celebrity has been commonly assessed by the 23-item Celebrity Attitude Scale (CAS). Recently, a 7-item short version (CAS-7) was developed on a representative sample of Hungarian adults. This study aimed to provide further evidence for the validity and reliability of the CAS-7 measure by extending the investigation of its factor structure to other cultures and populations. Methods Data from 4,353 participants (64.4% women, Mage = 28.22 years, SD = 11.80, age range: 14–93 years) across five countries (Canada, Hungary, Indonesia, Iran, US) were used, which was collected through online questionnaires. Results Consistent with previous findings, the bifactor structure with celebrity worship as a general factor and entertainment–social and intense–pathological specific factors showed the best fit in all samples. Reliability indices for the celebrity worship general factor were good. Conclusions The present findings confirmed the reliability and the consistency of the factor structure of the CAS-7 across different samples, providing further evidence for the applicability of the CAS-7 in different cultures.